Kinetic Analysis of the Metabotropic Glutamate Subtype 5 Tracer [18F]FPEB in Bolus and Bolus-Plus-Constant-Infusion Studies in Humans. Issue 4 (April 2013) - Sullivan, Jenna M; Lim, Keunpoong; Labaree, David; Lin, Shu-fei; McCarthy, Timothy J; Seibyl, John P; Tamagnan, Gilles; Huang, Yiyun; Carson, Richard E; Ding, Yu-Shin; Morris, Evan D
[ 18 F]FPEB is a positron emission tomography tracer which, in preclinical studies, has shown high specificity and selectivity toward the metabotropic glutamate receptor 5 (mGluR5). It possesses the potential to be used in human studies to evaluate mGluR5 function in a range of neuropsychiatric disorders, such as anxiety and Fragile X syndrome. To define optimal scan methodology, healthy human subjects were scanned for 6 hours following either a bolus injection ( n = 5) or bolus-plus-constant-infusion ( n = 5) of [ 18 F]FPEB. Arterial blood samples were collected and parent fraction measured by high-performance liquid chromatography (HPLC) to determine the metabolite-corrected plasma input function. Time activity curves were extracted from 13 regions and fitted by various models to estimate V T and BP ND . [ 18 F]FPEB was well fitted by the two-tissue compartment model, MA1 ( t ∗ = 30), and MRTM (using cerebellum white matter as a reference). Highest V T values were observed in the anterior cingulate and caudate, and lowest V T values were observed in the cerebellum and pallidum. For kinetic modeling studies, V T and BP ND were estimated from bolus or bolus-plus-constant-infusion scans as short as 90 minutes. Bolus-plus-constant-infusion of [ 18 F]FPEB reduced intersubject variability in V T and allowed equilibrium analysis to be completed with a 30-minute scan, acquired 90–120 minutes after the start of injection.